Societal attidude toward diarrhoeal diseases and bacteriological lest results of faeces in Yogyakarta - Trihendrokesowo, Trihendrokesowo (Universitas Gadjah Mada, 1987)
Nine-hundred eighty eight diarrhoeal disease patients of general hospitals, Public Health services and physicians in Yogyakarta during the period of January to October 1985 have been investigated. The results indicated that 75.20% of the patients were suffering diarrhoea of more than one day, and 83.10% with more than three times diarrhoea frequency in one day. In addition to diarrhoea symptoms, in more than 50% patients they were accompanied by abdominal pain and fever. Four point two percent of the patients received electrolyte and sugar solution before treatment. Examinations of faecal materials uncovered the presence of various bacteria suspected to be the causative agents of diarrhoea] diseases namely Vibrio parahaemolyticu.s, Vibrio choleree, Shigella flexneri, Salmonella enteritidis and E. coll. Key Words: diarrhoea] disease Ã¢â¬â abdominal pain Ã¢â¬â fever – electrolyte solution Ã¢â¬â bacteriology